Pengaruh Waktu Fermentasi Terhadap Kadar Bioetanol Dari Kulit Jagung Manis (Zea mays saccharata) - Agustina M., Renni; Ratman, Ratman; Said, Irwan (Jurnal Akademika Kimia, 2016)
This study aimed to determine the effect of fermentation time on the level of bioethanol from sweet corn bark. Sweet corn bark is one of the agricultural wastes containing cellulose which can be converted to bioethanol through several stapes. The steps were sample preparation, delignification, hydrolysis, and fermentation. This study applied fermentation process on the sweet corn bark using yeast bread (saccharomyces cereviseae) with time variations i.e 2-8 days.The products of fermented ethanol increasedand reached the optimum at 6 days fermentation with the bioethanol level of 4.50,then decrease the ethanol content at day 7 and 8.